O sentido do estudo para os alunos de graduação em administração e as percepções dos agentes envolvidos nesse processo - Moura, Leandro Souza (2012)
The higher education‟s census, conducted in 2009, showed that administration is the biggest undergraduate course in the country in number of enrollments. Adding classroom course and distance learning there are 1,102,579 students enrolled (18.5% of enrollments in higher education). In addition, enrollment in business administration courses grew 51% between 2005 and 2009. Due to the representativeness of the course, is not to be disregarded the sense of study for students seeking a bachelor's degree in business administration. Neither can‟t be neglected the congruence between the meaning assigned to the course by these students and the goals of the agents involved in planning and implementing of these courses. These agents are: the government, represented by the Ministry of Education and Culture (MEC), the profession‟s council, represented, at the state level, by the Rio de Janeiro‟s Regional Council of Administration (CRA-RJ), Higher Education Institutions (IES), Administrations course‟s coordinators, teachers, and finally, students. Based on the fact that each of these agents has its own goals and interests and thinking about students as recipients of the policies and practices performed by all agents involved in the process, it is intended, in this study to answer the following question: which are the meaning of study for the business administration students from Rio de Janeiro and the perceptions of those involved in this process? The field research was held in higher education institutions from Rio de Janeiro that offers business administration courses. Nine course coordinators, 17 teachers and 58 students were interviewed, totaling 84 respondents. The interviews were transcribed and analyzed using content analysis method. The survey concludes that the meaning attributed to the course by students is related to employability, and those involved in the administrator‟s formation, in its majority, have been adapting to it instead of leading and offering a broader sense to the course.